DETERMINAN MUTU PROSES DAN HASIL PEMBELAJARAN PENDIDIKAN KESETARAAN - Joko Sutarto (Universitas Negeri Malang, 2016)
Abstract: Factors Determing the Quality of Learning Process and Aoutcomes. This study aims to find out the influence of predisposing factors, the leadership of the head of Sanggar Kerja Bersama (Study Groups), work climate, financing, and infrastructure to the quality of the learning process and achievement of Package C Equivalence Education. This study found that; (a) leadership factor contributed a direct, dominant influence to the quality process (tutors' performance in designing their instructional plans) with a percentage of 51.84%; (b) leadership factor contributed a direct, dominant influence to the quality process (tutors' performance in implementing their instructional plans) with a percentage of 44.89%; (c) predisposing factors contributed a direct, dominant influence to the program participants' learning outputs with a percentage of 18.49%; (d) tutors' design of instructional plans directly put a great impact on their instructional performance with a percentage of 45%; the percentage of the tutors' design of instructional plans impact on the Package C participants' outputs was 20.25% whilst the percentage of the tutors' implementation of instructional plans impact on the Package C participants' outputs was 40.96%. Abstrak: Determinan Mutu Proses dan Hasil Pembelajaran Pendidikan Kesetaraan.  Penelitian ini bertujuan menganalisis pengaruh faktor predisposisi, kepemimpinan kepala Sanggar Kerja Bersama, iklim kerja, pembiayaan, dan sarana prasarana pembelajaran terhadap mutu proses dan hasil pembelajaran pendidikan kesetaraan paket C. Hasil penelitian menunjukan (a) faktor kepemimpinan memberi pengaruh langsung paling dominan terhadap mutu pembelajaran sebesar 51,84%, disusul faktor predisposisi 12,25%, sarana prasarana pembelajaran10,24%, iklim kerja 11,56%, dan faktor pembiayaan 0,81%; (b) faktor predisposisi memberi pengaruh langsung paling dominan terhadap perolehan hasil belajar sebesar 18,49%, disusul faktor sarana prasarana 17,64%, kepemimpinan 16,81%, iklim kerja 4,00%, dan faktor pembiayaan memberi 3,24%; dan (c) mutu pelaksanaan pembelajaran memberi pengaruh langsung terhadap hasil belajar sebesar 40,96%, sedangkan pengaruh langsung mutu perencanaan pembelajaran terhadap hasil belajar sebesar 20,25%.